2016
DOI: 10.3758/s13415-016-0443-2
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty and insula activation during uncertain reward

Abstract: Individuals with high intolerance of uncertainty (IU) have been shown to exhibit abnormal threat responding, which may be mediated by hyperactive anterior insula (aINS) response to uncertainty. Research has indicated that individuals with high IU also exhibit abnormal positive valence responding, suggesting that IU may impact responding to uncertainty regardless of the valence of the potential outcome. To date, no study has investigated the neural processes associated with IU and response to uncertain positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…At the moment, it is still under debate whether the striatum solely responds to salience or might encode both salience and valence of a stimulus (Bartra et al, 2013). The anterior insula, which has dense interconnections with the striatum (Ghaziri et al, 2018), has been implicated in encoding outcome uncertainty (Gorka et al, 2016), which is a key process of the anticipation phase of the SID design. Furthermore, the insula is a key node of the salience network (Menon and Uddin, 2010) and processes ascending interoceptive and visceromotor signals (Ronchi et al, 2015).…”
Section: Brain Regions Involved In the Anticipation Of Social Rewardsmentioning
confidence: 99%
“…At the moment, it is still under debate whether the striatum solely responds to salience or might encode both salience and valence of a stimulus (Bartra et al, 2013). The anterior insula, which has dense interconnections with the striatum (Ghaziri et al, 2018), has been implicated in encoding outcome uncertainty (Gorka et al, 2016), which is a key process of the anticipation phase of the SID design. Furthermore, the insula is a key node of the salience network (Menon and Uddin, 2010) and processes ascending interoceptive and visceromotor signals (Ronchi et al, 2015).…”
Section: Brain Regions Involved In the Anticipation Of Social Rewardsmentioning
confidence: 99%
“…We created this conceptual category to include tasks investigating the anticipation of a stimuli with an unknown valence (e.g., Sarinopoulos et al, 2010;Schienle et al, 2010;Klumpers et al, 2015) or an unpredictable reward (e.g., Bjork & Hommer, 2007;Gorka, et al, 2016), paradigms exploring feelings of anxiety elicited to temporally unpredictable presentations of a stimulus (e.g., Somerville et al, 2013;Shankman et al 2014). We also included tasks involving anticipation of aversive stimuli with randomized probabilities and unpredictable administration cued by a context (e.g., Alvarez et al, 2015;.…”
Section: Basic Threat and Reward Uncertaintymentioning
confidence: 99%
“…However, to date, very few studies have directly examined the distinction and overlap of this neurobiological sensitivity to cues and uncertainty in intense positive and negative valence events. The studies that have examined both reward and threat cue processing do suggest highly overlapping neurobiological and psychological processing abnormalities in anxiety disorders that may generally encompass the attribution of value and recruitment of attention to valenced cues, rather than just threat cues (Gorka, Nelson, Phan, & Shankman, 2016;Tanovic et al, 2018). In particular, one human study demonstrated that uncertain rewards, similar to threats, result in increased insula responsivity (Gorka et al, 2016).…”
Section: Cue Sensitivity and Sensitization By Stressmentioning
confidence: 99%
“…The studies that have examined both reward and threat cue processing do suggest highly overlapping neurobiological and psychological processing abnormalities in anxiety disorders that may generally encompass the attribution of value and recruitment of attention to valenced cues, rather than just threat cues (Gorka, Nelson, Phan, & Shankman, 2016;Tanovic et al, 2018). In particular, one human study demonstrated that uncertain rewards, similar to threats, result in increased insula responsivity (Gorka et al, 2016). Interestingly, although there are dopaminergic neurons that encode for just positive or negative motivational events, there are more numerous dopaminergic neurons that excite similarly to both threatening and rewarding events (Matsumoto & Hikosaka, 2009).…”
Section: Cue Sensitivity and Sensitization By Stressmentioning
confidence: 99%